The Relationship between Didactics and Social Skills:An Analytical Study - Aram Rasul Hussen; Jawan Ismail Bakr (Zanco Journal of Human Sciences, 2026)
The purpose of this study is to analyze the relationship between educational (didactic) methods and the development of social skills among students, with a focus on the impact of modern teaching methods on the development of their social skills. The descriptive formal approach was adopted as the basic framework for investigating this relationship, through the analysis of theoretical concepts related to didactics and social interaction. The theoretical analysis indicates that the use of modern didactic methods in the education process contributes significantly to the improvement of students’ social skills, such as cooperation, problem solving and effective communication. The study has emphasized the importance of providing an educational environment that encourages group interaction and discussion, which supports positive relationship building among students and enhances their adaptability to future work environments. The study showed that didactic methods based on group participation and discussion are relevant in enhancing students' social skills. It also shows that teachers can have a positive impact on this process by using teaching strategies that encourage active participation and teamwork, helping students to acquire the social skills that will be necessary for them in the labor market and society. Based on the results, it was recommended that the education system should focus more on enhancing the social skills of teachers in teaching programs by integrating interactive and group activities that encourage students to participate and collaborate